Registered health problems and demographic profile of integrated textile factory workers in Ethiopia: a cross-sectional study - Yifokire Tefera Zele; Abera Kumie; Wakgari Deressa; Magne Bråtveit; Bente E. Moen (BMC, 2021)
Abstract Background Textile and garment factories are growing in low and middle-income countries as worldwide demand for inexpensive clothing increases each year. These integrated textile and garment production factories are often built-in areas with few workplaces and environmental regulations, and employees can be regularly exposed to workplace hazards with little regulatory oversight. Consequently, workers' health may be significantly affected due to long term exposure to hazards. This study describes registered health problems and their association to work-related and personal factors among workers in integrated textile factories in Ethiopia. Methods Institution-based cross-sectional study design was employed for this analysis. A one-year recording of worker's clinical diagnoses (between March 2016 and February 2017) was gathered from the factory clinics of three integrated textile factories. Clinical diagnosis data was obtained as factory workers visited the clinics if feeling unwell. Sociodemographic characteristics and work-related information were obtained from the factory's human resource departments. The sociodemographic and clinical diagnosis statuses of 7992 workers were analyzed. The association between the registered diagnoses and workplace factors (work in textile production, garment production and support process) and personal factors (age, sex and educational status) were studied using logistic regression analysis. Results The average employee age and years of service were 40 years and 11 years respectively. 60% of workers were females, comprising of 4778 women. 66% of all workers (5276) had 27,320 clinical diagnoses. In total, this caused 16,993 absent working days due to sick leave. Respiratory diseases (34%) and musculoskeletal disorders (29%) were the most prevalent diagnoses, while bodily injuries were the cause of most work absences. Work department, sex and educational status are variables that were most significantly associated with higher prevalence of disease groups. Conclusions About two-thirds of the integrated textile factory workers were diagnosed with different types of disease. The textile and garment production department workers were affected at a greater rate than the support process workers, indicating that some diseases may be related to workplace exposure. Further study should investigate rare chronic diseases such as cancer, heart diseases, renal diseases and diabetes.